Fiber concrete. Prospects for development and application (Международный научный журнал «Инженер», 2026)
In the article the author presents the main features and advantages of using fiber-reinforced concrete in themanufacture of various building structures. The features preventing the wider use of fiber-reinforced concreteare given. An analysis of the influence of various factors in the manufacture of structures on the mechanicalproperties of fiber-reinforced concrete made it possible to evaluate the differences in its operation in the stretchedand compressed zone of structures. Recommendations are given on improving the mechanical characteristics offiber-reinforced concrete and an analysis of the work of other researchers on this issue.